Gender aspect of politeness strategies in spontaneous dialogical speech - Xakimova, Zumradxon (The Lingua Spectrum, 2025)
This article analyzes the gender-related features of politeness strategies in spontaneous dialogic speech. It examines how men and women differ in using positive and negative politeness strategies and how these reflect social and pragmatic functions in communication. The study is based on the theoretical framework of Brown and Levinson (1987), Leech (1983), Holmes (2013), and Tannen (1990). the framework of gender linguistics, it is noted that women and men use different speech strategies during communication. Based on Leech’s politeness theory, the study examines the ways in which male and female speakers employ speech methods aimed at “face-saving” and maintaining social harmony in natural dialogue. The research method involves analyzing examples from a corpus of spontaneous conversations. It was found that women tend to emphasize politeness more, while men are more likely to use direct strategies. In conclusion, it is highlighted that gender-specific politeness strategies depend on the social status of the interlocutors, their attitude towards the situation, and individual language culture. The results contribute to a deeper understanding of gender-based communicative differences and offer theoretical and practical insights applicable in linguistics, pragmatics, and social psychology.